Perbandingan Efektivitas Kompres Warm Water Tepid Sponge Dan Plester Demam Terhadap Penurunan Suhu Tubuh Pada Anak Pre-School Dengan Febris Di Puskesmas Tanah Abang Jakarta Tahun 2023 - Kofifah Sulistia Handayani; Hari Ghanesia Istiani; Yani Handayani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
This research highlights the comparison of the effectiveness of warm water tepid sponge compresses and fever plasters on body temperature in pre-school children with Febris at the Tanah Abang District Health Center, Jakarta, which will be carried out from December 2023 to January 2024. This research uses a quantitative approach with a Two research design Group Pretest Posttest. The sample for this research consisted of 32 pre- school children who would be divided into 2 groups, for each compress treatment with inclusion & exclusion criteria. The instrument used was an observation sheet in the form of a table check list regarding the SOP for implementing warm water tepid sponge compresses and fever plaster compresses. As well as an observation sheet in the form of a body temperature observation sheet before, during and after the warm water tepid sponge compress and fever plaster. Research Results Description of the temperature before and after using a warm water tepid sponge compress before it was 38,530C and after it was 37,370C and using a Plaster Compress before it was 38,350C and after it was 37,660C. The results of the dependent t statistical test showed that the warm water tepid sponge had a p value of 0.000 and the Fever Plaster had a p value of 0.000, meaning that there was an effect of warm water tepid sponge compresses and fever plasters on body temperature in pre-school children with Febris at the Tanah Abang District Health Center, Jakarta. will be carried out in December 2023. The results of the independent T test show that the p value is 0.000, so there is a difference between the Warm water tepid sponge Compress group and the Fever Plaster group on the body temperature of pre-school children with fever at the Tanah Abang District Health Center and compresses using the warm water tepid sponge technique are more effective in reducing body temperature. The difference in degrees of reduction in body temperature is -0.481.